More than sperm and egg: male, female and environmental factors that influence reproduction of Aedes and Anopheles mosquitoes - Alfonso-Parra, Catalina; Osorio, Jéssica; Agudelo, Juliana; Díaz, Sebastián; Ramírez-Sánchez, Luis; Avila, Frank (Revista Colombiana de Entomología, 2022)
Reproduction is more than the union of the sperm and the egg, as the successful generation of progeny requires a series of interactions (behavioral, physical, and molecular) between males and females to ensure that a spermatozoon will ultimately fertilize an egg. Thus, reproduction is a complex process in which species- and sex-specific behavioral cues are required for the localization, recognition, and attraction of a sexual partner, and post-insemination interactions between male and female molecules mediate physiological and behavioral changes in females necessary for optimal reproductive output. In this review, we focus on the behavioral and physiological processes required for reproduction in Aedes and Anopheles vector mosquitoes. We highlight recent work that has elucidated the pre-mating behaviors of males and females that lead to a successful copulation, describe the post-mating behavioral and physiological changes observed in females, which primarily serve to facilitate the production of progeny, and discuss the role of sex-specific molecules in mediating the post-mating changes observed in mated Aedes and Anopheles females. Finally, we give an overview of how environmental factors (e.g., larval nutrition or the composition of the microbiome) can influence adult fertility.